Foreign inventors in the US: Testing for Diaspora and Brain Gain Effects - Stefano Breschi; Francesco Lissoni; Ernest Miguelez (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We assess the role of ethnic ties in the diffusion of technical knowledge by means of a database of patent filed by US-resident inventors of foreign origin, which we identify through name analysis. We consider ten important countries of origin of highly skilled migration to the US, both Asian and European, and test whether foreign inventors' patents are disproportionately cited by: (i) co-ethnic migrants ('diaspora' effect); and (ii) inventors residing in their country of origin ('brain gain' effect). We find evidence of the diaspora effect for Asian countries, but not for European ones, with the exception of Russia. Diaspora effects do not translate necessarily into a brain gain effect, most notably for India; nor brain gain occurs only in presence of diaspora effects. Both the diaspora and the brain gain effects bear less weight than other knowledge transmission channels, such as co-invention networks and multinational companies.
Keywords: F22; O15; O31; 330; migration; brain gain; diaspora; diffusion; inventors; patents